(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The high solid content acrylic emulsion with a low viscosity is achieved by copolymerization of methylmethacrylate (MMA) and butylacrylate (BA) through emulsion polymerization method. By adopting the semi continuous copolymerization method of methylmethacrylate and butylacrylate, it was found that the 63% solid content resin can be prepared through this polymerization in presence of water soluble initiator (Potassium Persulphate, KPS) and Sodium Lauryl Sulfate (SLS) is used as a emulsifier . The effect of the initiator concentration, monomer to solvent ratio on solid content was studied. The copolymer was characterized by Fourier Transform Infrared (FTIR) spectroscopy. The thermal stability of synthesized resins was studied by Thermo Gravimetric Analyzer (TGA). The high solid content acrylic emulsion mostly used as a binder in water borne paint formulations because its having less volatile organic compound (VOC) which provides environmental protection and exhibits an excellent film formation ability and appearance.